Preparation method of polyphenylene sulfide-based thermoplastic composite prepreg and corresponding prepreg

By adding dopamine to the suspension system of polyamic acid and ammonia water, and deaming and cyclizing at high temperature to form polyimide, the problem of surfactant degradation of prepregs of polyphenylene sulfide thermoplastic composite materials at high temperature is solved. , achieving high quality of prepreg and excellent mechanical properties of composite materials.

CN119463247AActive Publication Date: 2025-02-18SICHUAN UNIV

Patent Information

Application Number
CN202411469570.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-02-18
Estimated Expiration
2044-10-21

AI Technical Summary

Technical Problem

When preparing polyphenylene sulfide-based thermoplastic composite prepreg, the high melting point and high melt viscosity of polyphenylene sulfide make it difficult to guarantee the quality of the prepreg. Traditional surfactants decompose at high temperatures and cause internal defects, which affects the mechanical properties .

Method used

By forming a suspended dispersion system containing polyamic acid and ammonia water, dopamine is added to the system, carbon fiber is added after filtering and precipitation, stable polyphenylene sulfide thermoplastic composite prepreg is prepared. Polyamic acid deamination and cyclization at high temperatures form highly heat-resistant polyimides, avoiding the degradation problem of traditional surfactants.

Benefits of technology

The uniform dispersion and long-term stability of polyphenylene sulfide powder are achieved, the defect of surfactant degradation at high temperature is avoided, and the quality of the prepreg and the mechanical properties of the composite material are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463247A_ABST
    Figure CN119463247A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a polyphenylene sulfide-based thermoplastic composite prepreg and a corresponding prepreg, and the preparation method specifically comprises the following steps: (1) preparing a suspension dispersion system containing polyphenylene sulfide, polyamide acid and ammonia water, and (2) preparing the prepreg containing polyimide, and adding a dopamine derivative in the step (2) for dispersion. The polyamic acid and the dopamine jointly improve the dispersity of the polyphenylene sulfide, the mechanical property of the composite material is improved, and the polyphenylene sulfide thermoplastic composite material has a good application prospect and can be used as a polyphenylene sulfide thermoplastic composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of engineering materials, and in particular to a preparation method of a polyphenylene sulfide-based thermoplastic composite material prepreg and the corresponding prepreg. Background Art

[0002] High-performance thermoplastic composites with continuous carbon fiber as reinforcement material and polyphenylene sulfide as matrix are widely used in aerospace, automotive industry, electronics and other fields due to their excellent mechanical properties, chemical stability and high temperature resistance.

[0003] In the preparation process of high-performance thermoplastic composite materials, the fibers need to be evenly dispersed in the polymer resin matrix to form a prepreg, which is then hot-pressed and hot-formed into a specific part. The quality of the prepreg is crucial to the mechanical properties of the part. However, given the high melting point and high melt viscosity of polyphenylene sulfide, it is very difficult to obtain high-quality thermoplastic composite prepregs. In order to overcome the above problems, a variety of preparation methods for heat-resistant polymer thermoplastic composite prepregs have emerged in recent years, among which the aqueous suspension impregnation technology has attracted attention due to its environmental protection and high cost-effectiveness.

[0004] A stable and uniform powder suspension is one of the technical difficulties of wet powder impregnation. Due to the high surface energy and hydrophobicity of polymer powder, it is necessary to add surfactants to the system to assist in forming a uniform and stable suspension. For example, patent CN108004779A uses polyacrylamide dispersants and alkylphenol polyoxyethylene ether as stabilizers to achieve the preparation of polyetherimide resin-based powder suspensions. However, the processing temperature of polyphenylene sulfide thermoplastic composites is ≥300°C, and surfactants such as polyacrylamide or polyoxyethylene ether are prone to degradation at this processing temperature, resulting in internal defects and affecting the mechanical properties of composite materials and their products. In addition, these surfactants are physically adsorbed on the surface of polymer powders through weak interactions such as van der Waals forces, and the long-term stability of the suspension is insufficient, which has a negative impact on the product uniformity and stability of composite prepregs. Surfactant residues have poor compatibility with the resin matrix and affect the interface. Summary of the invention

[0005] In view of the deficiencies of the prior art, the present invention provides a polyphenylene sulfide thermoplastic composite material prepreg and a preparation method thereof.

[0006] The preparation method comprises: step (1): preparing a suspension dispersion system comprising polyphenylene sulfide, polyamic acid and ammonia water, and step (2): preparing a prepreg comprising polyimide.

[0007] Step (1) is to add amino-terminated polyamic acid into ammonia water, dissolve the ammonium salt formed by the polyamic acid and ammonia water, and add polyphenylene sulfide to form a stable suspension dispersion system;

[0008] Step (2) specifically includes adding dopamine strong acid salt into the suspension system, filtering out the precipitate, dispersing it in ammonia water and dissolving it, and adding carbon fiber to obtain the prepreg.

[0009] The ammonium salt formed by polyamic acid and ammonia water dissolves, and the generated electrostatic repulsion promotes the dispersion of polymer powder.

[0010] After the impregnation is completed, heating promotes the decomposition and removal of the ammonium salt, and the polyamic acid undergoes imidization to form a highly heat-resistant polyimide, avoiding the defects caused by the degradation of traditional heat-sensitive small molecule or large molecule surfactants during high-temperature processing.

[0011] Furthermore, a method for preparing a polyphenylene sulfide thermoplastic composite material prepreg comprises the following steps:

[0012] (S1) reacting dianhydride or partial anhydride with diamine to synthesize polyamic acid, controlling the molar ratio of the synthetic feed materials, obtaining amino-terminated polyamic acid, precipitating, washing, and drying;

[0013] (S2) adding polyamic acid into aqueous ammonia to fully dissolve it;

[0014] (S3) adding polyphenylene sulfide powder to the system and continuing stirring;

[0015] (S4) adding a strong acid salt of dopamine such as dopamine hydrochloride to the system to deposit dopamine and polyamic acid on the surface of the polyphenylene sulfide powder; separating the powder by filtration, washing, and drying for later use;

[0016] (S5) dispersing the powder in aqueous ammonia, stirring sufficiently to dissolve the deposited polyamic acid, forming a stable polyphenylene sulfide powder dispersion, and transferring the dispersion to an immersion tank for later use;

[0017] (S6) The carbon fiber is subjected to a fiber spreading treatment and sequentially passed through an impregnation tank, a high-temperature drying tunnel and a compaction roller to obtain a polyphenylene sulfide composite material prepreg.

[0018] Furthermore, the dianhydride or partial anhydride used in step S1 includes but is not limited to 1,2,4-trimethylenetetracarboxylic anhydride, 3,3,4,4-biphenyltetracarboxylic anhydride, 3,3,4,4-benzophenonetetracarboxylic anhydride, bicyclo[2.2.2]oct-7-ene-2,3,5,6-tetracarboxylic anhydride, pyromellitic anhydride, 4,4'-(4,4'-isopropyldiphenyloxy)phthalic anhydride and combinations thereof.

[0019] Furthermore, the diamines used in step S1 include but are not limited to 4,4-diaminodiphenylmethane, p-phenylenediamine, 4,4-diaminobenzophenone, diaminomethylcyclohexylmethane, 4,4-diaminodiphenyl ether, m-tolidine, m-phenylenediamine, α,α'-di(4-aminophenyl)-1,4-diisopropylbenzene and combinations thereof.

[0020] Furthermore, in step S1, the molar ratio of diamine to dianhydride or partial anhydride is 1.01 to 1.1, preferably 1.03 to 1.08.

[0021] Furthermore, the structure of the water-based polyamic acid synthesized in step S1 is as follows:

[0022]

[0023] Furthermore, the mass content of aqueous ammonia in step S2 is in the range of 2%-10%, preferably in the range of 5-8%, and the mass ratio of aqueous ammonia to polyphenylene sulfide is 3.3-20, preferably 8-10.

[0024] Furthermore, in step S2, the amount of polyamic acid added is 0.67%-40% of the polyphenylene sulfide, preferably 10%-15%.

[0025] Furthermore, in step S4, the amount of dopamine hydrochloride added is 0.67%-20% of the mass of the polyphenylene sulfide, preferably 1%-6%.

[0026] Furthermore, step S4 is preferably carried out in an open environment to maintain sufficient oxygen.

[0027] Furthermore, a catalyst may be added in step S4 to accelerate the copolymerization rate of dopamine and polyamic acid, and preferred catalysts include ferrous chloride and sodium periodate.

[0028] Furthermore, the treatment time in step S4 is 30 min-4 h, preferably 2 h-4 h.

[0029] Furthermore, in step S5, the mass ratio of ammonia water to the polyphenylene sulfide powder treated by deposition of dopamine and polyamic acid is 3.3-20, preferably 3.57-4.55.

[0030] Furthermore, the high-temperature drying tunnel in step S6 adopts a stepped temperature setting, with the starting temperature of the drying tunnel being 90-120°C and the ending temperature of the drying tunnel being 280-300°C.

[0031] The present invention also claims a prepreg prepared by the above method.

[0032] In addition, a use of the above-mentioned prepreg is to obtain a polyphenylene sulfide thermoplastic composite laminate by laminating and hot pressing the prepreg, and further use it for aircraft parts such as fairings, flaps, wing leading edges, and cabin floors; automobile interior and exterior parts such as doors, hoods, and fenders; electronic and electrical parts such as laptop computer shells and mobile phone back panels, or laminate the prepreg with other components (for example, honeycomb cores) to produce fiber-reinforced composite materials, or laminate the prepreg with other components to produce fiber-reinforced composite materials, such as honeycomb sandwich panels.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] 1) The polyamic acid deposited on the surface of the polyphenylene sulfide powder forms polyamic acid ammonium salt in ammonia water, and its huge charge repulsion effect can make the polyphenylene sulfide powder evenly dispersed to form a suspension;

[0035] 2) The ammonium salt of polyamic acid acts as a surfactant, which can undergo deamination and cyclization at high temperatures to form highly heat-resistant polyimide, which can avoid the internal defects of the material formed by the degradation of heat-sensitive small molecule or macromolecular surfactants used in traditional methods during high-temperature processing, and improve the quality of the prepreg;

[0036] 3) Unlike the traditional method of blending surfactants and polymer powders only by physical adsorption, dopamine and polyamic acid are copolymerized and deposited. The high adhesion of the polydopamine copolymer network improves the binding force between polyamic acid and polyphenylene sulfide powder, which can improve the long-term stability of polyphenylene sulfide powder slurry and improve the quality stability and uniformity of prepregs;

[0037] 4) The polyimide formed by the cyclization of polyamic acid can enhance the interfacial bonding between polyphenylene sulfide resin and fiber and improve the mechanical properties of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 Schematic diagram of polyamic acid-dopamine deposition of polyphenylene sulfide particles

[0039] Figure 2 Changes in infrared spectral characteristics of polyimide formed by heating polyamic acid DETAILED DESCRIPTION

[0040] The technical scheme in the specific embodiment of the present invention is described in detail and completely below. Obviously, the described embodiment is only a part of the specific implementation of the overall technical scheme of the present invention, rather than all implementations. Based on the overall concept of the present invention, all other embodiments obtained by ordinary technicians in this field fall within the scope of protection of the present invention.

[0041] Embodiment 1:

[0042] (1) Weigh 114.63 g of p-phenylenediamine (114.63 g / 108.14 g / mol = 1.06 mol), 192.12 g of 1,2,4-benzene trimethylene anhydride (192.12 g / 192.12 g / mol = 1 mol), and 2 L of N-methylpyrrolidone. Add p-phenylenediamine to N-methylpyrrolidone and stir at room temperature for 30 min to fully dissolve the diamine. Then, add 1,2,4-benzene trimethylene anhydride in five portions within four hours. After stirring at room temperature for 10 hours, pour the solution into water to terminate the reaction. Repeat the soaking-filtration washing with deionized water for three times, and obtain polyamic acid powder after drying.

[0043] (2) Weigh 1 kg of polyphenylene sulfide powder, 5 kg of 5% ammonia water, and 80 g of polyamic acid powder. Add the polyamic acid powder to the ammonia water and stir until fully dissolved. Then add the polyphenylene sulfide powder and stir mechanically for 30 minutes at a stirring speed of 300 rpm.

[0044] (3) Weigh 30 g of dopamine hydrochloride and add it to the reaction solution. Stir continuously for 4 h in an open environment while keeping the container open at a stirring speed of 200 rpm.

[0045] (4) The mixed solution is filtered to obtain polyphenylene sulfide powder co-precipitated with dopamine and polyamic acid, and the powder is repeatedly soaked and filtered and washed with deionized water for three times.

[0046] (5) Weigh 1 kg of polyphenylene sulfide powder treated with dopamine and polyamic acid deposition, add it to 4 kg of 5% ammonia water, continue stirring to fully dissolve the polyamic acid, form a stable polyphenylene sulfide powder dispersion, and transfer it to an immersion tank for later use.

[0047] (6) Install 6 rolls of carbon fiber on the yarn frame, and enter the impregnation tank after the yarn spreading treatment. The impregnated fiber is introduced into the heating drying tunnel, the temperature is set at 100°C-200°C-290°C, and the pulling speed is 1m / min to obtain prepreg.

[0048] (7) The prepreg is laminated and hot-pressed at a temperature of 300°C and a pressure of 0.5 MPa.

[0049] (8) The fiber content, interlaminar shear strength, tensile strength and tensile modulus, and porosity of the laminated composite materials were tested. The specific results are listed in Table 1.

[0050] Embodiment 2:

[0051] (1) Weigh 105.98 g of p-phenylenediamine (105.98 g / 108.14 g / mol = 0.98 mol), 192.12 g of 1,2,4-benzene trimethylene glycol (192.12 g / 192.12 g / mol = 1 mol), and 2 L of N-methylpyrrolidone. Add p-phenylenediamine to N-methylpyrrolidone and stir at room temperature for 30 min to fully dissolve the diamine. Then, add 1,2,4-benzene trimethylene glycol in five portions over four hours. After stirring at room temperature for 10 hours, pour the solution into water to terminate the reaction. Repeat the soaking-filtration washing with deionized water for three times, and obtain polyamic acid powder after drying.

[0052] (2) Weigh 1 kg of polyphenylene sulfide powder, 5 kg of 5% ammonia water, and 80 g of polyamic acid powder. Add the polyamic acid powder to the ammonia water and stir until fully dissolved. Then add the polyphenylene sulfide powder and stir mechanically for 30 minutes at a stirring speed of 300 rpm.

[0053] (3) Weigh 30 g of dopamine hydrochloride and add it to the reaction solution. Stir continuously for 4 h in an open environment while keeping the container open at a stirring speed of 200 rpm.

[0054] (4) The mixed solution is filtered to obtain polyphenylene sulfide powder co-precipitated with dopamine and polyamic acid, and the powder is repeatedly soaked and filtered and washed with deionized water for three times.

[0055] (5) Weigh 1 kg of polyphenylene sulfide powder treated with dopamine and polyamic acid deposition, add it to 4 kg of 5% ammonia water, continue stirring to fully dissolve the polyamic acid, form a stable polyphenylene sulfide powder dispersion, and transfer it to an immersion tank for later use.

[0056] (6) Install 6 rolls of carbon fiber on the yarn frame, and enter the impregnation tank after the yarn spreading treatment. The impregnated fiber is introduced into the heating drying tunnel, the temperature is set at 100°C-200°C-290°C, and the pulling speed is 1m / min to obtain prepreg.

[0057] (7) The prepreg is laminated and hot-pressed at a temperature of 300°C and a pressure of 0.5 MPa.

[0058] (8) The fiber content, interlaminar shear strength, tensile strength and tensile modulus, and porosity of the laminated composite materials were tested. The specific results are listed in Table 1.

[0059] Embodiment 3:

[0060] (1) Weigh 114.63 g of p-phenylenediamine (114.63 g / 108.14 g / mol = 1.06 mol), 192.12 g of 1,2,4-benzene trimethylene glycol (192.12 g / 192.12 g / mol = 1 mol), and 2 L of N-methylpyrrolidone. Add p-phenylenediamine to N-methylpyrrolidone and stir at room temperature for 30 min to fully dissolve the diamine. Then add 1,2,4-benzene trimethylene glycol in five portions over four hours. After stirring at room temperature for 10 hours, pour the solution into water to terminate the reaction. Repeat the soaking-filtration washing with deionized water for three times, and obtain polyamic acid powder after drying.

[0061] (2) Weigh 1 kg of polyphenylene sulfide powder, 5 kg of 5% ammonia water, and 80 g of polyamic acid powder. Add the polyamic acid powder to the ammonia water and stir until fully dissolved. Then add the polyphenylene sulfide powder and stir mechanically for 30 minutes at a stirring speed of 300 rpm.

[0062] (3) Weigh 30 g of dopamine hydrochloride and add it to the reaction solution. Stir continuously for 4 h in an open environment while keeping the container open at a stirring speed of 200 rpm.

[0063] (4) The mixed solution is filtered to obtain polyphenylene sulfide powder co-precipitated with dopamine and polyamic acid, and the powder is repeatedly soaked and filtered and washed with deionized water for three times.

[0064] (5) Weigh 1 kg of polyphenylene sulfide powder treated with dopamine and polyamic acid deposition, add it to 4 kg of deionized water, and continue stirring to fully dissolve the polyamic acid to form a stable polyphenylene sulfide powder dispersion, which is then transferred to an immersion tank for later use.

[0065] (6) Install 6 rolls of carbon fiber on the yarn frame, and enter the impregnation tank after the yarn spreading treatment. The impregnated fiber is introduced into the heating drying tunnel, the temperature is set at 100°C-200°C-290°C, and the pulling speed is 1m / min to obtain prepreg.

[0066] (7) The prepreg is laminated and hot-pressed at a temperature of 300°C and a pressure of 0.5 MPa.

[0067] (8) The fiber content, interlaminar shear strength, tensile strength and tensile modulus, and porosity of the laminated composite materials were tested. The specific results are listed in Table 1.

[0068] Embodiment 4:

[0069] (1) Weigh 114.63 g of p-phenylenediamine (114.63 g / 108.14 g / mol = 1.06 mol), 192.12 g of 1,2,4-benzene trimethylene glycol (192.12 g / 192.12 g / mol = 1 mol), and 2 L of N-methylpyrrolidone. Add p-phenylenediamine to N-methylpyrrolidone and stir at room temperature for 30 min to fully dissolve the diamine. Then add 1,2,4-benzene trimethylene glycol in five portions over four hours. After stirring at room temperature for 10 hours, pour the solution into water to terminate the reaction. Repeat the soaking-filtration washing with deionized water for three times, and obtain polyamic acid powder after drying.

[0070] (2) Weigh 1 kg of polyphenylene sulfide powder, 5 kg of 5% ammonia water, and 80 g of polyamic acid powder. Add the polyamic acid powder to the ammonia water and stir until fully dissolved. Then add the polyphenylene sulfide powder and stir mechanically for 30 minutes at a stirring speed of 300 rpm.

[0071] (3) Weigh 30 g of dopamine hydrochloride and add it to the reaction solution. Seal the reaction container and continue stirring for 10 h at a stirring speed of 200 rpm.

[0072] (4) The mixed solution is filtered to obtain polyphenylene sulfide powder co-precipitated with dopamine and polyamic acid, and the powder is repeatedly soaked and filtered and washed with deionized water for three times.

[0073] (5) Weigh 1 kg of polyphenylene sulfide powder treated with dopamine and polyamic acid deposition, add it to 4 kg of 5% ammonia water, continue stirring to fully dissolve the polyamic acid, form a stable polyphenylene sulfide powder dispersion, and transfer it to an immersion tank for later use.

[0074] (6) Install 6 rolls of carbon fiber on the yarn frame, and enter the impregnation tank after the yarn spreading treatment. The impregnated fiber is introduced into the heating drying tunnel, the temperature is set at 100°C-200°C-290°C, and the pulling speed is 1m / min to obtain prepreg.

[0075] (7) The prepreg is laminated and hot-pressed at a temperature of 300°C and a pressure of 0.5 MPa.

[0076] (8) The fiber content, interlaminar shear strength, tensile strength and tensile modulus, and porosity of the laminated composite materials were tested. The specific results are listed in Table 1.

[0077] Embodiment 5:

[0078] (1) Weigh 114.63 g of p-phenylenediamine (114.63 g / 108.14 g / mol = 1.06 mol), 192.12 g of 1,2,4-benzene trimethylene glycol (192.12 g / 192.12 g / mol = 1 mol), and 2 L of N-methylpyrrolidone. Add p-phenylenediamine to N-methylpyrrolidone and stir at room temperature for 30 min to fully dissolve the diamine. Then add 1,2,4-benzene trimethylene glycol in five portions over four hours. After stirring at room temperature for 10 hours, pour the solution into water to terminate the reaction. Repeat the soaking-filtration washing with deionized water for three times, and obtain polyamic acid powder after drying.

[0079] (2) Weigh 1 kg of polyphenylene sulfide powder, 5 kg of 5% ammonia water, and 80 g of polyamic acid powder. Add the polyamic acid powder to the ammonia water and stir until fully dissolved. Then add the polyphenylene sulfide powder and stir mechanically for 30 minutes at a stirring speed of 300 rpm.

[0080] (3) Weigh 10 g of dopamine hydrochloride and add it to the reaction solution. Stir continuously for 4 h in an open environment while keeping the container open at a stirring speed of 200 rpm.

[0081] (4) The mixed solution is filtered to obtain polyphenylene sulfide powder co-precipitated with dopamine and polyamic acid, and the powder is repeatedly soaked and filtered and washed with deionized water for three times.

[0082] (5) Weigh 1 kg of polyphenylene sulfide powder treated with dopamine and polyamic acid deposition, add it to 4 kg of 5% ammonia water, continue stirring to fully dissolve the polyamic acid, form a stable polyphenylene sulfide powder dispersion, and transfer it to an immersion tank for later use.

[0083] (6) Install 6 rolls of carbon fiber on the yarn frame, and enter the impregnation tank after the yarn spreading treatment. The impregnated fiber is introduced into the heating drying tunnel, the temperature is set at 100°C-200°C-290°C, and the pulling speed is 1m / min to obtain prepreg.

[0084] (7) The prepreg is laminated and hot-pressed at a temperature of 300°C and a pressure of 0.5 MPa.

[0085] (8) The fiber content, interlaminar shear strength, tensile strength and tensile modulus, and porosity of the laminated composite materials were tested. The specific results are listed in Table 1.

[0086] Embodiment 6:

[0087] (1) Weigh 114.63 g of p-phenylenediamine (114.63 g / 108.14 g / mol = 1.06 mol), 192.12 g of 1,2,4-benzene trimethylene glycol (192.12 g / 192.12 g / mol = 1 mol), and 2 L of N-methylpyrrolidone. Add p-phenylenediamine to N-methylpyrrolidone and stir at room temperature for 30 min to fully dissolve the diamine. Then add 1,2,4-benzene trimethylene glycol in five portions over four hours. After stirring at room temperature for 10 hours, pour the solution into water to terminate the reaction. Repeat the soaking-filtration washing with deionized water for three times, and obtain polyamic acid powder after drying.

[0088] (2) Weigh 1 kg of polyphenylene sulfide powder, 5 kg of 5% ammonia water, and 20 g of polyamic acid powder, add the polyamic acid powder to the ammonia water, stir until fully dissolved, add the polyphenylene sulfide powder, and mechanically stir for 30 minutes at a stirring speed of 300 rpm.

[0089] (3) Weigh 30 g of dopamine hydrochloride and add it to the reaction solution. Stir continuously for 4 h in an open environment while keeping the container open at a stirring speed of 200 rpm.

[0090] (4) The mixed solution is filtered to obtain polyphenylene sulfide powder co-precipitated with dopamine and polyamic acid, and the powder is repeatedly soaked and filtered and washed with deionized water for three times.

[0091] (5) Weigh 1 kg of polyphenylene sulfide powder treated with dopamine and polyamic acid deposition, add it to 4 kg of 5% ammonia water, continue stirring to fully dissolve the polyamic acid, form a stable polyphenylene sulfide powder dispersion, and transfer it to an immersion tank for later use.

[0092] (6) Install 6 rolls of carbon fiber on the yarn frame, and enter the impregnation tank after the yarn spreading treatment. The impregnated fiber is introduced into the heating drying tunnel, the temperature is set at 100°C-200°C-290°C, and the pulling speed is 1m / min to obtain prepreg.

[0093] (7) The prepreg is laminated and hot-pressed at a temperature of 300°C and a pressure of 0.5 MPa.

[0094] (8) The fiber content, interlaminar shear strength, tensile strength and tensile modulus, and porosity of the laminated composite materials were tested. The specific results are listed in Table 1.

[0095] Embodiment 7:

[0096] (1) Weigh 114.63 g of p-phenylenediamine (114.63 g / 108.14 g / mol = 1.06 mol), 192.12 g of 1,2,4-benzene trimethylene glycol (192.12 g / 192.12 g / mol = 1 mol), and 2 L of N-methylpyrrolidone. Add p-phenylenediamine to N-methylpyrrolidone and stir at room temperature for 30 min to fully dissolve the diamine. Then add 1,2,4-benzene trimethylene glycol in five portions over four hours. After stirring at room temperature for 10 hours, pour the solution into water to terminate the reaction. Repeat the soaking-filtration washing with deionized water for three times, and obtain polyamic acid powder after drying.

[0097] (2) Weigh 1 kg of polyphenylene sulfide powder, 5 kg of 5% ammonia water, and 90 g of polyamic acid powder. Add the polyamic acid powder to the ammonia water and stir until fully dissolved. Then add the polyphenylene sulfide powder and stir mechanically for 30 minutes at a stirring speed of 300 rpm.

[0098] (3) Weigh 30 g of dopamine hydrochloride and 2 g of ferrous chloride, add them to the reaction solution, and stir continuously for 30 min at a speed of 200 rpm in an open environment while keeping the container open.

[0099] (4) The mixed solution is filtered to obtain polyphenylene sulfide powder co-precipitated with dopamine and polyamic acid, and the powder is repeatedly soaked and filtered and washed with deionized water for three times.

[0100] (5) Weigh 1 kg of polyphenylene sulfide powder treated with dopamine and polyamic acid deposition, add it to 4 kg of 5% ammonia water, continue stirring to fully dissolve the polyamic acid, form a stable polyphenylene sulfide powder dispersion, and transfer it to an immersion tank for later use.

[0101] (6) Install 6 rolls of carbon fiber on the yarn frame, and enter the impregnation tank after the yarn spreading treatment. The impregnated fiber is introduced into the heating drying tunnel, the temperature is set at 100°C-200°C-290°C, and the pulling speed is 1m / min to obtain prepreg.

[0102] (7) The prepreg is laminated and hot-pressed at a temperature of 300°C and a pressure of 0.5 MPa.

[0103] (8) The fiber content, interlaminar shear strength, tensile strength and tensile modulus, and porosity of the laminated composite materials were tested. The specific results are listed in Table 1.

[0104] Embodiment 8:

[0105] (1) Weigh 114.63 g of p-phenylenediamine (114.63 g / 108.14 g / mol = 1.06 mol), 192.12 g of 1,2,4-benzene trimethylene glycol (192.12 g / 192.12 g / mol = 1 mol), and 2 L of N-methylpyrrolidone. Add p-phenylenediamine to N-methylpyrrolidone and stir at room temperature for 30 min to fully dissolve the diamine. Then add 1,2,4-benzene trimethylene glycol in five portions over four hours. After stirring at room temperature for 10 hours, pour the solution into water to terminate the reaction. Repeat the soaking-filtration washing with deionized water for three times, and obtain polyamic acid powder after drying.

[0106] (2) Weigh 1 kg of polyphenylene sulfide powder, 5 kg of 5% ammonia water, and 80 g of polyamic acid powder. Add the polyamic acid powder to the ammonia water and stir until fully dissolved. Then add the polyphenylene sulfide powder and stir mechanically for 30 minutes at a stirring speed of 300 rpm.

[0107] (3) Weigh 30 g of dopamine hydrochloride and add it to the reaction solution. Stir continuously for 30 min at a stirring speed of 200 rpm in an open environment while keeping the container open.

[0108] (4) The mixed solution is filtered to obtain polyphenylene sulfide powder co-precipitated with dopamine and polyamic acid, and the powder is repeatedly soaked and filtered and washed with deionized water for three times.

[0109] (5) Weigh 1 kg of polyphenylene sulfide powder treated with dopamine and polyamic acid deposition, add it to 4 kg of 5% ammonia water, continue stirring to fully dissolve the polyamic acid, form a stable polyphenylene sulfide powder dispersion, and transfer it to an immersion tank for later use.

[0110] (6) Install 6 rolls of carbon fiber on the yarn frame, and enter the impregnation tank after the yarn spreading treatment. The impregnated fiber is introduced into the heating drying tunnel, the temperature is set at 100°C-200°C-290°C, and the pulling speed is 1m / min to obtain prepreg.

[0111] (7) The prepreg is laminated and hot-pressed at a temperature of 300°C and a pressure of 0.5 MPa.

[0112] (8) The fiber content, interlaminar shear strength, tensile strength and tensile modulus, and porosity of the laminated composite materials were tested. The specific results are listed in Table 1.

[0113] Comparative Example 1:

[0114] (1) Weigh 1 kg of polyphenylene sulfide resin, 0.4 kg of polyoxyethylene octanol ether, and 3 kg of deionized water, add them into a dispersion barrel, stir at a speed of 2000 rpm, and stir for 240 minutes.

[0115] (2) Transfer the prepared slurry into a dipping tank for later use.

[0116] (3) Install 6 rolls of carbon fiber on the yarn frame, and enter the impregnation tank after the yarn spreading treatment. Introduce the impregnated fiber into the heating drying tunnel, set the temperature at 100℃-200℃-290℃, and the pulling speed at 1m / min to obtain prepreg.

[0117] (4) The prepreg is laminated and hot-pressed at a temperature of 300°C and a pressure of 0.5 MPa.

[0118] (5) The fiber content, interlaminar shear strength, tensile strength and tensile modulus, and porosity of the laminated composite materials were tested. The specific results are listed in Table 1.

[0119] Comparative Example 2:

[0120] (1) Weigh 1 kg of polyphenylene sulfide powder, 5 kg of 5% ammonia water, and 20 g of polyamic acid powder. Add the polyamic acid powder to the ammonia water and stir until fully dissolved. Then add the polyphenylene sulfide powder and stir mechanically for 30 minutes at a stirring speed of 300 rpm.

[0121] (3) Weigh 30 g of dopamine hydrochloride and add it to the reaction solution. Stir continuously for 4 h in an open environment while keeping the container open at a stirring speed of 200 rpm.

[0122] (4) The mixed solution is filtered to obtain polyphenylene sulfide powder co-precipitated with dopamine and polyamic acid, and the powder is repeatedly soaked and filtered and washed with deionized water for three times.

[0123] (5) Weigh 1 kg of polyphenylene sulfide powder treated with dopamine and polyamic acid deposition, add it to 4 kg of 5% ammonia water, continue stirring to fully dissolve the polyamic acid, form a stable polyphenylene sulfide powder dispersion, and transfer it to an immersion tank for later use.

[0124] (6) Install 6 rolls of carbon fiber on the yarn frame, and enter the impregnation tank after the yarn spreading treatment. The impregnated fiber is introduced into the heating drying tunnel, the temperature is set at 100°C-200°C-290°C, and the pulling speed is 1m / min to obtain prepreg.

[0125] (7) The fiber content, interlaminar shear strength, tensile strength and tensile modulus, and porosity of the laminated composite materials were tested. The specific results are listed in Table 1.

[0126] Comparative Example 3:

[0127] (1) Weigh 114.63 g of p-phenylenediamine (114.63 g / 108.14 g / mol = 1.06 mol), 192.12 g of 1,2,4-benzene trimethylene glycol (192.12 g / 192.12 g / mol = 1 mol), and 2 L of N-methylpyrrolidone. Add p-phenylenediamine to N-methylpyrrolidone and stir at room temperature for 30 min to fully dissolve the diamine. Then add 1,2,4-benzene trimethylene glycol in five portions over four hours. After stirring at room temperature for 10 hours, pour the solution into water to terminate the reaction. Repeat the soaking-filtration washing with deionized water for three times, and obtain polyamic acid powder after drying.

[0128] (2) Weigh 1 kg of polyphenylene sulfide powder, 4 kg of 5% ammonia water, and 80 g of polyamic acid powder, add the polyamic acid powder to the ammonia water, stir until fully dissolved, add the polyphenylene sulfide powder, and mechanically stir for 2 hours at a stirring speed of 300 rpm to form a polyphenylene sulfide powder dispersion, which is transferred to an impregnation tank for later use.

[0129] (3) Install 6 rolls of carbon fiber on the yarn frame, and enter the impregnation tank after the yarn spreading treatment. The impregnated fiber is introduced into the heating drying tunnel, the temperature is set at 100°C-200°C-290°C, and the pulling speed is 1m / min to obtain prepreg.

[0130] (4) The prepreg is laminated and hot-pressed at a temperature of 300°C and a pressure of 0.5 MPa.

[0131] (5) The fiber content, interlaminar shear strength, tensile strength and tensile modulus, and porosity of the laminated composite materials were tested. The specific results are listed in Table 1.

[0132] Table 1 Comparison of test results of prepregs prepared in Example and Comparative Example

[0133]

[0134]

[0135] *Every 50m of prepreg is sampled, hot pressed, and its fiber content is tested. The average value is taken to evaluate the stability of the prepreg quality.

[0136] It can be seen from the above embodiments that in Embodiments 1 and 2, the best effect is obtained by using a diamine to dianhydride or partial anhydride ratio of 1.06:1 in Embodiment 1, and a diamine to dianhydride ratio of 0.98:1 in Embodiment 2. Molecules containing amino groups can participate in the polymerization reaction of dopamine, but acid anhydride end-capping cannot. When the polyamic acid is not completely end-capped with amino groups, the reaction effect of the polyamic acid and dopamine and the subsequent dispersion effect cannot be guaranteed.

[0137] In Example 1 and Example 3, in step (5) of Example 1, ammonia water is used as the dispersion medium of the polyphenylene sulfide powder. The alkaline environment promotes the hydrolysis of the carboxyl groups in the polyamic acid, which can promote the dissolution of the polyamic acid. The ammonia water forms an ammonium salt with the carboxyl groups, and the huge electrostatic repulsion between the ammonium salt groups ensures the uniform dispersion of the polyphenylene sulfide powder. In step (5) of Example 3, deionized water is used as the dispersion medium of the polyphenylene sulfide powder. In a neutral environment, the polyamic acid cannot be fully hydrolyzed and ionized, the stability of the suspension system is insufficient, and the uniformity and long-term stability of the prepared prepreg are not as good as those in Example 1.

[0138] Compared with Example 4, the polymerization of dopamine in Example 1 requires the participation of oxygen. In Example 1, step (3) is an open system that can ensure sufficient supply of oxygen to polymerize dopamine, while in Example 4, it is a closed environment with insufficient oxygen, and the polymerization of dopamine is hindered. Therefore, the amino-terminated polyamic acid fails to fully bind to the surface of polyphenylene sulfide, affecting the stability of the suspension system and the quality of the prepreg.

[0139] Compared with Example 5, Example 1 has a smaller amount of dopamine in Example 5, and the amino-terminated polyamic acid fails to fully bond to the surface of polyphenylene sulfide. The stability of the suspension system and the quality of the prepreg are not as good as those in Example 1.

[0140] Compared with Example 6, Example 1 has a smaller amount of polyamic acid used in Example 6, and fewer polyamic acid molecules are connected to the surface of the polyphenylene sulfide powder, which is not conducive to the uniform dispersion of the polyphenylene sulfide powder and ultimately affects the quality of the prepreg.

[0141] Compared with Example 7, the addition of ferrous chloride in Example 1 can catalyze the polymerization of dopamine. Therefore, step (3) in Example 7 is only reacted for 30 minutes. The performance of the prepreg finally prepared is equivalent to that of the prepreg prepared under the reaction conditions of 4 hours in Example 1. Ferrous chloride can greatly shorten the process time.

[0142] Compared with Example 8, Example 1 was reacted for only 30 minutes in Example 8, the amount of polydopamine and polyamic acid bound to the surface of the polyphenylene sulfide powder was small, and the stability of the polyphenylene sulfide powder suspension system was insufficient.

[0143] Compared with Comparative Example 1, in Comparative Example 1, polyoxyethylene octanol ether is used as a surfactant, and the prepared prepreg has better quality stability. However, due to the insufficient thermal stability of polyoxyethylene octanol ether, degradation occurs during the molding process of the composite material, introducing defects, resulting in higher porosity and lower mechanical properties of the composite material.

[0144] Compared with Example 1 and Comparative Example 2, in Comparative Example 2, only dopamine is used without introducing polyamic acid, and the electrostatic repulsion of the ammonium salt formed by the polyamic acid is lacking, the stability of the polyphenylene sulfide powder suspension system is poor, and the stability of the mass content of the prepreg is poor.

[0145] Compared with Example 1 and Comparative Example 3, in Comparative Example 3, only polyamic acid is used without dopamine. Polyamic acid cannot form a strong bond with polyphenylene sulfide with the help of polydopamine, but can only form a weak bond through van der Waals interaction, etc., which ultimately leads to insufficient stability of the polyphenylene sulfide suspension system.

[0146] in addition, Figure 1 Schematic diagram of polyamic acid and dopamine treating polyphenylene sulfide powder. Polyamic acid is fully dissolved in ammonia water to form polyamic acid ammonium salt. After adding dopamine and polyphenylene sulfide powder, the amine functional group of the end group of polyamic acid ammonium salt participates in the polymerization process of dopamine, thereby being fixed on the surface of polyphenylene sulfide powder. The positive and negative ions on the molecular chain of polyamic acid form a huge electrostatic repulsion, which helps polyphenylene sulfide to be evenly dispersed.

[0147] Figure 2 The infrared spectrum characteristic changes of polyamic acid before and after heating. 1550cm -1 The absorption peak at 1780cm is the coupling of NH bond deformation and CN bond stretching of amide bond, which represents the characteristic absorption of polyamide acid. -1 The characteristic vibration mode of the imide ring represents the characteristic absorption of polyimide. -1 There is strong absorption, which disappears after heating and forms strong absorption at 1780, which means that polyamic acid is converted into polyimide by heating.

Claims

1. A method for preparing a polyphenylene sulfide-based thermoplastic composite prepreg, characterized in that: The steps include: Step (1): preparing a suspension dispersion system comprising polyphenylene sulfide, polyamic acid and ammonia water, and step (2): preparing a prepreg comprising polyimide, and adding a dopamine derivative for dispersion in step (2).

2. The preparation method according to claim 1, characterized in that: The preparation method specifically comprises: step (1) adding amino-terminated polyamic acid to ammonia water, dissolving the ammonium salt formed by the polyamic acid and ammonia water, and adding polyphenylene sulfide to form a stable suspension dispersion system; Step (2) is to add dopamine strong acid salt into the suspension system, filter out the precipitate, disperse it in ammonia water and dissolve it, add carbon fiber, impregnate and heat it to obtain the prepreg.

3. The preparation method according to claim 2, characterized in that: In step (1), the ammonium salt formed by the polyamic acid and ammonia water is dissolved, and the generated electrostatic repulsion promotes the dispersion of the polymer powder.

4. The preparation method according to claim 2, characterized in that: After the impregnation in step (2) is completed, heating is used to promote the decomposition and removal of the ammonium salt, and the polyamic acid undergoes imidization to form a highly heat-resistant polyimide, thereby avoiding the defects caused by the degradation of traditional heat-sensitive small molecule or large molecule surfactants during high-temperature processing.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The following steps are included (S1) reacting dianhydride or partial anhydride with diamine to synthesize polyamic acid, controlling the molar ratio of the synthetic feed materials, obtaining amino-terminated polyamic acid, precipitating, washing, and drying; (S2) adding polyamic acid into aqueous ammonia to fully dissolve it; (S3) adding polyphenylene sulfide powder to the system and continuing stirring; (S4) adding a strong acid salt of dopamine such as dopamine hydrochloride to the system to deposit dopamine and polyamic acid on the surface of the polyphenylene sulfide powder; separating the powder by filtration, washing, and drying for later use; (S5) dispersing the powder in aqueous ammonia, stirring sufficiently to dissolve the deposited polyamic acid, forming a stable polyphenylene sulfide powder dispersion, and transferring the dispersion to an immersion tank for later use; (S6) The carbon fiber is subjected to a fiber spreading treatment and sequentially passed through an impregnation tank, a high-temperature drying tunnel and a compaction roller to obtain a polyphenylene sulfide composite material prepreg.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The dianhydride or partial anhydride used in step S1 includes but is not limited to 1,2,4-trimellitic anhydride, 3,3,4,4-biphenyltetracarboxylic anhydride, 3,3,4,4-benzophenonetetracarboxylic anhydride, bicyclo[2.2.2]oct-7-ene-2,3,5,6-tetracarboxylic anhydride, pyromellitic anhydride, 4,4'-(4,4'-isopropyldiphenyloxy) diphthalic anhydride and combinations thereof; The diamine used in step S1 includes, but is not limited to, 4,4-diaminodiphenylmethane, p-phenylenediamine, 4,4-diaminobenzophenone, diaminomethylcyclohexylmethane, 4,4-diaminodiphenyl ether, m-tolidine, m-phenylenediamine, α,α'-di(4-aminophenyl)-1,4-diisopropylbenzene and combinations thereof; In step S1, the molar ratio of diamine to dianhydride or partial anhydride is 1.01 to 1.1, preferably 1.03 to 1.

08.

7. The preparation method according to any one of claims 1 to 5, characterized in that: The structure of the water-based polyamic acid synthesized in step S1 is as follows:

8. The preparation method according to any one of claims 1 to 5, characterized in that: The mass content of aqueous ammonia in step S2 is in the range of 2%-10%, preferably in the range of 5-8%, and the mass ratio of aqueous ammonia to polyphenylene sulfide is 3.3-20, preferably 8-10; Further, in step S2, the amount of polyamic acid added is 0.67%-40% of polyphenylene sulfide, preferably 10%-15%; Furthermore, in step S4, the amount of dopamine hydrochloride added is 0.67%-20% of the mass of polyphenylene sulfide, preferably 1%-6%; Furthermore, step S4 is preferably carried out in an open environment to maintain sufficient oxygen; Furthermore, a catalyst may be added in step S4 to accelerate the copolymerization rate of dopamine and polyamic acid, and preferred catalysts include ferrous chloride and sodium periodate; Further, the treatment time in step S4 is 30min-4h, preferably 2h-4h; Furthermore, in step S5, the mass ratio of ammonia water to the polyphenylene sulfide powder treated by dopamine and polyamic acid deposition is 3.3:1 to 20:1, preferably 3.57:1 to 4.55:1; Furthermore, the high-temperature drying tunnel in step S6 adopts a stepped temperature setting, with the starting temperature of the drying tunnel being 90-120°C and the ending temperature of the drying tunnel being 280-300°C.

9. A polyphenylene sulfide-based thermoplastic composite prepreg, characterized in that: The preparation method is adopted according to any one of claims 1 to 8.

10. A use of the above-mentioned prepreg, by laminating and hot pressing the prepreg according to claim 9 to obtain a polyphenylene sulfide thermoplastic composite laminate, and further used for aircraft parts such as fairings, flaps, wing leading edges, cabin floors; automobile interior and exterior parts such as doors, hoods, fenders; electronic and electrical parts such as laptop computer shells and mobile phone back panels, or laminating the prepreg according to claim 9 with other components (for example, honeycomb cores) to produce fiber-reinforced composite materials, or laminating the prepreg according to claim 9 with other components to produce fiber-reinforced composite materials, such as honeycomb sandwich panels.

Citation Information

Patent Citations

  • Polyaryletherketone resin-based suspension sizing agent for carbon fibers and preparation method thereof

    CN108004779A

  • High-thermal-conductivity reinforced polyphenylene sulfide composite material and preparation method thereof

    CN112322039A

  • Fiber-reinforced polyarylene sulfide copolymer composite substrate, method for producing same, and molded article containing same

    CN114206990A

  • Carbon fiber reinforced thermoplastic polyphenylene sulfide resin-based composite material and preparation method thereof

    CN115141485A

  • Polyphenylene sulfide fabric for alkaline water electrolysis and preparation method

    CN117904870A

Cited By

  • Preparation method of fiber cloth reinforced polyphenylene sulfide alloy prepreg sheet, composite board and preparation method and application of composite board

    CN120588531A